Austenitic stainless steel capable of being subjected to heat treatment and precipitation strengthening and manufacturing method and application thereof
By reasonably adding alloy elements to austenitic stainless steel and performing heat treatment, solid solution strengthening and precipitation strengthening of the material is achieved, solving the problem of degradation of toughness and corrosion resistance of existing austenitic stainless steel after heat treatment, improving the mechanical properties and service life of the material, and saving nickel resources.
Patent Information
- Application Number
- CN202311186284.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2025-03-21
AI Technical Summary
The toughness and corrosion resistance of existing austenitic stainless steels after heat treatment are deteriorated and cannot be strengthened through heat treatment, resulting in increased material thickness, difficult welding, waste of resources and increased risk of stress corrosion.
By reasonably combining alloying elements such as nitrogen (N), tungsten (W), vanadium (V), niobium (Nb), cobalt (Co) and rare earth (RE), microalloy smelting is carried out, and the forged and rolled material is subjected to appropriate heat treatment to achieve solid solution strengthening and precipitation strengthening of the material.
It significantly improves the room temperature and high temperature mechanical properties of the material, reduces the overall investment of the material, saves nickel resources, reduces welding stress and corrosion risks, and extends the service life of the material.
Smart Images

Figure CN119663102A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of austenitic stainless steel, in particular to austenitic stainless steel capable of heat treatment and precipitation strengthening, and a manufacturing method and application thereof. Background Art
[0002] 300 series stainless steel is an alloy material containing iron, carbon, nickel and chromium (or chromium + molybdenum). It is non-magnetic and has good forging and rolling formability and corrosion resistance. Relatively speaking, 3 series austenitic stainless steels including 304, 304L, 304LN, 310, 316, 316L, 317L, 321, 347, etc. are economical and have good pressure bearing and corrosion resistance. Therefore, pressure vessels and pressure pipelines in industries such as petroleum refining, coal chemical industry, medicine, chemical industry, nuclear power, hydrogen energy, LNG, etc. are mostly made of 3 series stainless steel, which better adapts to the higher pressure and higher temperature environment of pressure vessels and pipelines during use. However, 300 series stainless steel contains more Ni, and my country's Ni resources are not abundant, so a large amount of imports are required, and Ni is expensive.
[0003] The strengthening mechanism of metal materials is usually strain strengthening, solid solution strengthening, fine grain strengthening and precipitation strengthening. However, 300 series stainless steel cannot be strengthened by heat treatment. Even 321 and 347 stainless steels containing stabilizing elements will have dispersed carbides precipitated in the grains after stabilization heat treatment at 900°C. The effect of precipitation strengthening is extremely limited. Moreover, 3 series stainless steels without stabilizing elements will have carbides precipitated at the grain boundaries after heat treatment in the sensitization temperature range or high temperature use, which will greatly reduce their toughness and corrosion resistance. Since the yield strength of 300 series stainless steel in solid solution state is low, the material thickness used in design calculation is relatively large. Due to the physical properties of stainless steel, the corrosion resistance of 300 series stainless steel is greatly reduced. The physical characteristics of stainless steel are large thermal expansion coefficient and low thermal conductivity, which makes the welding heat input too concentrated. As the section thickness increases, repeated welding heat cycles increase the weld shrinkage. As a result, the welding stress is very large and there are many cases of welding crack failure. This not only greatly wastes the precious metal nickel in stainless steel, but also increases the difficulty of welding. At the same time, due to the sensitization and precipitation of carbides in austenitic stainless steel, it is not suitable for post-weld stress relief annealing treatment, resulting in many cases of stress failure, which correspondingly increases the risk of stress corrosion.
[0004] 300 series stainless steel can also learn from the principle of nickel-based alloys to add Ti, Nb, Co, Al, Cu, etc. through ultra-long precipitation of several hours and multiple heat treatments to precipitate fine dispersed particles such as γ'-Ni3Al, γ'-Ni3Ti, γ'-Ni3Nb uniformly distributed in the matrix to achieve the high strength characteristics of 300 series stainless steel, which has a significant strengthening effect on 300 series stainless steel. In order to achieve the purpose of second phase precipitation, the proportion of these strengthening phase elements added is often relatively high. These 300 series stainless steels need to be subjected to long-term aging heat treatment between 600 and 900 ° C to enable these strengthening phases to precipitate sufficiently. However, during the long-term aging treatment process, these strengthening phases are not only precipitated in the crystal, but also precipitated in large quantities at the grain boundary, resulting in a significant reduction in the toughness of the material, insufficient toughness reserve, and great difficulty in welding. At the same time, the energy consumption of precipitation hardening heat treatment for too long a time is very large, which does not conform to the innovative model of green development.
[0005] In the pressure vessel industry, it is generally believed that the presence of carbides and nitrides in 300 series stainless steel in the form of precipitation at grain boundaries is harmful. In order to avoid the precipitation of carbides and nitrides at grain boundaries, the aforementioned 3 series austenitic stainless steels are delivered in a solid solution state. In recent years, related invention patents at home and abroad, such as CN201810274149.7 "A super austenitic stainless steel and its alloy composition optimization design method", CN202111210754.6 "Super austenitic stainless steel with low precipitation phase precipitation and its preparation and heat treatment method", CN202211622720.2 "A method for preparing high-strength and high-plasticity austenitic stainless steel with medium nitrogen content" are not austenitic stainless steels that can be heat-treated and strengthened. The Mn content in the chemical composition of CN202180008641.X "Austenitic stainless steel" is very high (8-10%), and the key consideration is that the cation fraction in the passivation film must be ≥4.5. Among the 11 trace elements that can be added, B, Co, Ga, and ERW are not carbonitride-forming elements. It is impossible to achieve the purpose of heat treatment strengthening by using the free combination of these elements.
[0006] As pointed out on page 400 of the American Society for Metals Heat Treatment Handbook Volume D "Heat Treatment of Iron and Steel Materials", "conventional austenitic stainless steel cannot be strengthened by heat treatment", and on page 444 "high nitrogen austenitic stainless steel cannot be strengthened by heat treatment"; "Super Austenitic Stainless Steel and High Nickel Corrosion Resistant Alloys" pointed out on page 85 "nitrogen is harmful when it exists in the form of nitrides, but vanadium, niobium, and titanium are easy to form nitrides, so they cannot be used as elements to increase the solubility of nitrogen in steel". These statements have hindered metallurgical workers from conducting relevant research on precipitation strengthening of austenitic stainless steel.
[0007] In addition to strain strengthening, conventional austenitic stainless steel can achieve solid solution strengthening by adding carbon and nitrogen. However, there is a negative problem of sensitization precipitation during material hot processing and welding thermal cycle. The second phase of sensitization precipitation is generally M23C6, MN2, etc. Precipitation-strengthened austenitic stainless steel materials are usually considered unreliable or have catastrophic risks of intergranular corrosion and stress corrosion damage. Summary of the invention
[0008] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention is based on the precipitation strengthening theory, solid solution strengthening and heat treatment precipitation strengthening are carried out to develop a new cheap austenitic stainless steel material that can be heat-treated and strengthened. The present invention adds nitrogen N and nitride-forming elements tungsten W, vanadium V, niobium Nb, cobalt Co, rare earth RE, etc. for micro-alloying smelting through reasonable matching of alloy elements, and performs appropriate heat treatment on the finished material after forging and rolling to greatly improve the room temperature mechanical properties and high temperature mechanical properties of the material. When the high-strength stainless steel material produced by the present invention is used to manufacture related products, the thickness of the stainless steel material can be reduced, and the overall input of the stainless steel material can be greatly reduced, thereby saving the large-scale application of the strategic resource precious metal nickel in stainless steel, thereby achieving the purpose of resource saving, energy saving, and investment saving.
[0009] The present invention provides a heat-treatable precipitation-strengthened austenitic stainless steel, characterized in that the components of the austenitic stainless steel are as follows by weight percentage:
[0010] C≤0.05%;
[0011] Si≤1.0%;
[0012] Mn≤2.0%;
[0013] S≤0.015%;
[0014] P≤0.035%;
[0015] Cr 16.0~20.0%;
[0016] Ni 6.0~12.0%;
[0017] N 0.08~0.25%;
[0018] W 0.05~0.25%;
[0019] V 0.05~0.25%;
[0020] Any one or both of Nb and Ta 0.1-0.60%;
[0021] The balance is Fe and inevitable impurities.
[0022] Furthermore, it also includes Co, the weight percentage of which is 0 to 0.50%;
[0023] Furthermore, RE is included, and its weight percentage is 0 to 0.020%;
[0024] Furthermore, the N content is 2 times or more than the C content, and C+N should be ≥ 0.12%.
[0025] The present invention also discloses a method for manufacturing the austenitic stainless steel for pressure vessels capable of heat treatment and strengthening, which is characterized in that the 300 series stainless steel is refined in an electric furnace and outside the furnace, and the components are modulated according to the above formula.
[0026] The present invention also discloses a method for heat treatment strengthening of austenitic stainless steel for pressure vessels that can be heat treated and strengthened, which is characterized in that the austenitic stainless steel for pressure vessels that can be heat treated and strengthened is subjected to 1050°C insulation solid solution treatment and then water-cooled after being taken out of the furnace, and then subjected to strengthening heat treatment and air cooling, the heat treatment temperature is between 650 and 900°C, and the heat treatment time is 0.3-4 hours.
[0027] Furthermore, it is preferred that the heat treatment temperature is 800° C. for 4 hours and then the product is air-cooled, or the heat treatment temperature is 750° C. for 1 hour and then the product is air-cooled.
[0028] The invention also discloses the application of the austenitic stainless steel capable of heat treatment and strengthening for pressure vessels in manufacturing plates, forgings, pipes, bolts, nuts, welding wires and welding rods.
[0029] Preferably, the plates, forgings and pipes are welded to produce pressure vessels, heat exchangers, air coolers, atmospheric pressure vessels and structural products.
[0030] The heat-treatable precipitation-strengthened austenitic stainless steel of the present invention utilizes N, W, V and the like to play a microalloy solid solution strengthening and precipitation strengthening role on carbides and nitrides, thereby improving the tensile strength, yield strength, hardness and impact value of the material, and appropriately reducing the elongation to about 40%. The material process performance, i.e., processing performance, is good, and the material is less deformed by stress during use. The tank body, pressure vessel, heat exchanger, i.e., structural product, etc. in the petrochemical industry are particularly suitable for prestressed bolts and nuts and other opening and closing, detachable fastening connection systems that are stressed during use, thereby reducing the probability of loosening of the equipment, being reliable in use, having a long service life, and improving the material performance, thereby reducing the design thickness of the stainless steel material, and being able to replace the currently used 3 series stainless steel to save a large amount of nickel resources and reduce the material cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a microscopic metallographic image of the heat-treatable precipitation-strengthened austenitic stainless steel 3040A material provided by the present invention under an optical microscope;
[0032] Figure 2 This is a 200-fold metallographic image of the 3040A material provided by the present invention after heat treatment at 800°C / 4h under an electron microscope;
[0033] Figure 3 This is a 2000-fold metallographic image of the 3040A material provided by the present invention after heat treatment at 800°C / 4h under an electron microscope;
[0034] Figure 4 This is an electron microscope image of the 3040A material provided by the present invention after heat treatment at 800°C / 4h under a 5000x electron microscope, in which the mark 1 indicates the energy spectrum analysis detection point 1 of the second phase precipitate;
[0035] Figure 5 yes Figure 4 Energy spectrum analysis diagram of detection point 1
[0036] Figure 6 This is an electron microscope image of the 3040A material provided by the present invention after heat treatment at 800℃ / 4h under a 25000x electron microscope. Figure 2 , spectrum Figure 3 They represent the energy spectrum analysis detection points 2 and 3 of the second phase precipitates respectively;
[0037] Figure 7 yes Figure 6 Energy spectrum analysis diagram of detection point 2;
[0038] Figure 8 yes Figure 6 Energy spectrum analysis diagram of detection point 3;
[0039] Fig. 9 This is an electron microscope image of the 3040A material provided by the present invention after heat treatment at 800℃ / 4h under a 100000 times electron microscope. Figure 4 , spectrum Figure 5 They represent the energy spectrum analysis detection points 4 and 5 of the second phase precipitates respectively;
[0040] Fig.10 yes Fig. 9 Energy spectrum analysis diagram of detection point 4;
[0041] Fig.11 yes Fig. 9 Energy spectrum analysis diagram of detection point 5;
[0042] Fig.12 This is an electron microscope image of the 3040A material provided by the present invention after heat treatment at 800°C / 4h under a 100,000x electron microscope. Figure 6 , spectrum Figure 7 , spectrum Figure 8They represent the energy spectrum analysis detection points 6, 7, and 8 of the second phase precipitates respectively;
[0043] Fig.13 yes Fig.12 Energy spectrum analysis diagram of detection point 6;
[0044] Fig.14 yes Fig.12 Energy spectrum analysis diagram of detection point 7;
[0045] Fig.15 yes Fig.12 Energy spectrum analysis diagram of detection point 8;
[0046] Fig.16 This is an electron microscope image of the 3040A material provided by the present invention after heat treatment at 800°C / 4h under a 100,000x electron microscope. Fig. 9 Indicates the energy spectrum analysis detection point 9 of the second phase precipitate;
[0047] Fig.17 yes Fig.16 Energy spectrum analysis diagram of detection point 9;
[0048] Fig.18 A low-magnification metallographic image of a weld seam of 3040A solid solution state pipes provided by the present invention using ER347 welding wire argon arc welding;
[0049] Fig.19 A 200-fold metallographic diagram of the fusion zone of the 3040A solid solution state pipe provided by the present invention using ER347 welding wire argon arc welding;
[0050] Fig. 20 The present invention provides a low magnification metallographic image of a weld obtained by welding a 3040A pipe strengthened by a heat treatment at 750°C with a nickel-based welding wire of ERNiCrMo-3 (625). DETAILED DESCRIPTION
[0051] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0052] In the description of the present invention, it should be understood that the terms "center", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0053] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the solid solution state refers to the material obtained after solid solution at 1050°C / 1h+water cooling, and the terms "installed", "connected", and "set" should be understood in a broad sense, for example, it can be fixedly connected, set, or detachably connected, set, or integrally connected, set. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0054] Comparative Example 1
[0055] 304LN, 321 and 347H stainless steels are all improved stainless steel varieties based on conventional 304 stainless steel. In this comparative example 1, 304LN nitrogen-containing stainless steel, 321 titanium-containing stainless steel, and 347H niobium-containing stainless steel plates were selected for heat treatment tests to understand the performance and effect of solid solution strengthening and precipitation strengthening of existing conventional austenitic stainless steels.
[0056] Table 1 304LN, 321, 347H plate composition test results (%)
[0057] C Si Mn S P Cr Ni N Ti Nb 304LN 0.012 0.38 1.73 0.005 0.024 19.13 11.18 0.10 / / 321 0.036 0.59 1.25 0.001 0.024 17.08 9.248 / 0.60 / 347H 0.055 0.46 1.73 0.001 0.020 17.35 9.06 / / 0.48
[0058] According to the composition test results, the carbon content of 340LN is very low, and the precipitated phase is mainly chromium nitride; 321 and 347H do not contain nitrogen, 321 relies on Ti to stabilize, and the precipitated phase is mainly titanium carbide; 347H relies on Nb to stabilize C, and the precipitated phase is mainly niobium carbide.
[0059] The test plates are 304LN and 321 with a thickness of 20mm. They are subjected to a series of heat treatments, namely, 1050℃ solid solution insulation for 1h and water cooling (i.e., the current common solid solution delivery state), and then 750-900℃ insulation for 4h and air cooling. After heat treatment, the tensile strength, yield strength, elongation, hardness, and room temperature and ultra-low temperature impact tests are respectively carried out at room temperature. The test results are shown in Table 2 and Table 3:
[0060] Table 2 Test results of 304LN (nitrogen-containing) stainless steel after heat treatment
[0061]
[0062]
[0063] Through heat treatment tests, the yield strength of 304LN stainless steel decreased slightly after heat treatment at 850℃ and 900℃, and increased slightly at 750℃, but the strengthening effect was almost negligible.
[0064] Table 3 Test results of 321 (titanium-containing) stainless steel after heat treatment
[0065]
[0066] Through heat treatment tests, the yield strength of 321 stainless steel decreased slightly after heat treatment at 850℃ and 900℃, but the yield strength increased slightly after heat treatment at 750℃, but the tensile strength decreased. This shows that although titanium can stabilize the C in the material, it does not play a significant strengthening role.
[0067] Comparative Example 2
[0068] The 347H material with a thickness of 20mm was used for the test. It was subjected to a series of heat treatments, including 1050℃ solid solution insulation for 1h and water cooling (i.e. the current common solid solution delivery state), and then 700-850℃ insulation for 1h and air cooling. After the heat treatment, the tensile strength, yield strength, room temperature and ultra-low temperature impact tests were carried out at room temperature. The test results of various indicators are shown in Table 4:
[0069] Table 4 347H (containing niobium) stainless steel heat treatment test results
[0070]
[0071] Note: The test results in Table 4 are comparative tests conducted after the test results of the heat-treatable precipitation-hardened austenitic stainless steel of the present invention (Table 6) came out. It can be seen from Table 6 that whether it has the heat treatment strengthening effect can be determined by heat treatment insulation for 1 hour, so the insulation time of Comparative Example 2 is set to 1 hour.
[0072] From Table 4, it can be seen that the tensile strength of 347H is slightly improved after solution treatment at 1050°C for 1h, water cooling, and then stabilization heat treatment at 700-850°C for 1h, but the strengthening effect of yield strength is basically negligible.
[0073] According to the heat treatment test results of the above three stainless steel materials, the yield strength of 304LN is higher than that of 321 and 347H stainless steel in both solid solution state and other heat treatment states, and the order of yield strength is 304LN>347H>321, indicating that the solid solution strengthening effect of N in 304LN stainless steel is obvious, but these three grades of austenitic stainless steel do not have obvious heat treatment strengthening function.
[0074] In the "Experimental Study on Reheating Crack Sensitivity of Thick-walled TP347H Steel Pipe Welded Joints" by Wang Jianjun and others from Sinopec in the 7th issue of "Pressure Vessel" in 2022, it is introduced that TP347 steel has precipitation strengthening characteristics at high temperature, but during the heat treatment process and under high-temperature service, NbC will precipitate both in the grains and at the grain boundaries. Intracrystalline precipitation causes intracrystalline strengthening, which will relatively cause grain boundary weakening. The higher the temperature, the more intense the diffusion of elements to the grain boundaries, resulting in excessive NbC at the grain boundaries. Excessive precipitation phases will also cause local stress concentration, providing favorable conditions for the nucleation of holes at the grain boundaries. But in fact, the test results in Table 4 show that its precipitation strengthening effect is only beneficial to the improvement of tensile strength and hardness, and has no effect on yield strength. Moreover, the inventors also simulated the use conditions of 347H at 620℃ / 100H, and no actual effect of precipitation strengthening was found. Therefore, it is not very meaningful to carry out high-temperature strengthening heat treatment on the basis of 347 and 347H.
[0075] According to the conclusions of the above heat treatment research, the existing conventional austenitic stainless steel strengthening path through heat treatment is not feasible.
[0076] Example 1
[0077] Recipe Design
[0078] Precipitation-strengthened stainless steel designed with nitride combination based on 304. Based on the composition of 304 stainless steel, the carbon content is controlled, and appropriate amounts of N, W, V, Nb, etc. are added for solid solution strengthening and precipitation strengthening. Its composition design is:
[0079] C≤0.05%; Si≤1.0%; Mn≤2.0%; S≤0.015%; P≤0.035%; Cr / 16.0~20.0%;
[0080] Ni / 6~12.0%; N / 0.08~0.25%; W / 0.05~0.25%; V / 0.05~0.25%; Nb+Ta / 0.1~0.60%; the balance is Fe and inevitable residual elements.
[0081] The allowable amount of residual elements: Cu / ≤0.50%, Mo≤0.50%.
[0082] test
[0083] Ten groups of steel bars are rolled according to the chemical composition described in Table 5, or ten groups of 304 stainless steel are subjected to electric furnace + vacuum microalloying refining and modulation outside the furnace according to the chemical composition described in Table 5 and then forged and rolled to obtain stainless steel materials, the grade of which is tentatively set as 3040A.
[0084] Table 5 Chemical composition analysis of 3040A (%)
[0085]
[0086] The 3040A stainless steel billet smelted in Test 4 was selected and rolled into 10 bars with a diameter of 30 mm at high temperature. The bars were solution treated at 1050° for 1 hour and then water-cooled out of the furnace for solution heat treatment (i.e., the current common solution delivery state). After solution treatment, precipitation strengthening heat treatment was performed at 650°C to 900°C, and then tensile and hardness tests, as well as room temperature and ultra-low temperature impact tests were performed at room temperature. The test results are shown in Table 6:
[0087] Table 6 Results of heat treatment strengthening test on 3040A austenitic stainless steel
[0088]
[0089]
[0090] From the data in Table 6, it can be seen that the effect of solid solution strengthening is obvious when N, Nb, W and V are added in combination. The tensile strength of the material in the solid solution delivery state is 689MPa, and the yield strength is 333MPa. The tensile strength is higher than that of 321, 347H and 304LN, and the yield strength is significantly improved. The yield strength is 124MPa higher than that of 321 in the solid solution state, 98MPa higher than that of 347H in the solid solution state, and 46MPa higher than that of 304LN. The strength of 321 stainless steel is actually basically the same as that of 304. It can also be said that the yield strength of 3040A in the solid solution state is about 41.7% higher than that of 321 or 304 stainless steel, the elongation is appropriately reduced, and the hardness is greatly improved.
[0091] In the strengthening heat treatment test at different temperatures, the strength after heat treatment at 800℃ and 750℃ is the best, and the room temperature impact value is still as high as 200J or more, indicating that the performance is very superior and the micro-alloying composition design is very reasonable. The yield strength of 3040A after heat treatment at 750℃ / 1h rises to 438MPa, which is about 86.38% higher than the delivery state (solid solution) of 321 / 304.
[0092] Among all heat treatment tests of 3040A, the high temperature mechanical properties of 800℃ / 4h and 750℃ / 1h are the best, and the room temperature impact value and ultra-low temperature impact value can also maintain a good state, that is, the most preferred heat treatment temperature range is between 750℃ and 800℃ (±20)℃. From the comprehensive evaluation of energy saving and mechanical properties, the comprehensive performance of 750℃ / 1h heat treatment is the best.
[0093] Metallographic observation and energy spectrum analysis
[0094] The 3040A material obtained from Test 4 in Table 5 was solution treated at 1050°C for 1 h, then water-cooled out of the furnace + 800°C / 4h, and then air-cooled out of the furnace for metallographic observation and energy spectrum analysis.
[0095] Under an ordinary optical microscope, Figure 1 As shown in the figure, the microstructure of the 3040A material test 1 is a pure austenite structure with twins, without any ferrite residue. Pure austenitic stainless steel without ferrite residue has good high temperature resistance. Although the nitrogen carbide strengthening elements W, V, Nb are added, and the material is precipitated and strengthened by heat treatment, it can still maintain good ultra-low temperature performance at -196℃.
[0096] Observe through electron microscope at 200 times, such as Figure 2 As shown in Figure 1, nitrides are dispersed and precipitated in the grain, while there is no second phase precipitation and aggregation at the grain boundary; when magnified 2000 times, as shown in Figure 1 Figure 3 As shown, two kinds of very fine white precipitates of second phase particles can be observed in the crystal, one of which is micron-sized particles, the maximum size of which agglomerates together does not exceed 5μm, and the other is nanometer-sized particles, and there is no second phase precipitation at the grain boundary.
[0097] In order to facilitate further observation, the micron-sized precipitates were magnified to 5000 times by electron microscope for energy spectrum detection, such as Figure 4 and Figure 5 The electron microscope photo and spectrum of the precipitate particle 1 are shown Figure 1 No W was found in (detection point 1);
[0098] The nanoscale precipitates were magnified to 25,000 to 100,000 times for spectrum analysis, and the following results were obtained: Figure 6 , 9 , 12 and 16. At a magnification of 25,000 times Figure 6 It was found that there were many extremely fine precipitated particles dispersed in the crystal. Two detection points were selected for energy spectrum analysis, and the following results were obtained: Figure 7 Spectrum Figure 2 and Figure 8 Spectrum Figure 3 ; at 100,000 times magnification Fig. 9 In the above analysis, two detection points are selected for single nano-scale precipitate particles to perform energy spectrum analysis, and the following results are obtained: Fig.10 Spectrum Figure 4 and Fig.11 Spectrum Figure 5 ; at 100,000 times magnification Fig.12 In the above analysis, three detection points were selected for single nano-scale precipitates to perform energy spectrum analysis, and the following results were obtained: Fig.13 Spectrum Figure 6 , Fig.14 Spectrum Figure 7 and Fig.15 Spectrum Figure 8 ; at 100,000 times magnification Fig.16 A single nanoscale precipitate in the sample was selected at one detection point for energy spectrum analysis, and the following results were obtained: Fig.17 Spectrum Fig. 9 By computer interpretation of the specific proportions of each element in the above energy spectrum analysis diagram, the particle spectrum of the second phase precipitate Figure 1-9 The energy spectrum analysis results are shown in Table 7.
[0099] Table 7 Spectrum element composition weight percentage (%)
[0100] Spectrum C N W V Nb Cr Ni Fe 1 2.9 13.53 0 0.61 44.52 9.1 4.17 25.17 2 32.04 0 1.30 0 0 16.34 33.05 17.27 3 21.78 0 0.69 0.04 0 18.14 40.70 18.66 4 38.63 0 1.23 0 0 13.98 31.43 14.74 5 34.38 0 1.14 0 0 14.99 32.43 17.07 6 28.28 0 0.62 0.11 0 16.09 34.35 20.56 7 27.53 3.5 0.35 0.06 0 14.91 35.48 18.18 8 37.05 1.62 0.56 0.47 0 13.07 29.32 17.9 9 27.5 0 1.03 0 0 15.06 39.14 16.7
[0101] Figure 4 The metallographic image in Figure 2 shows that the size of particle 1 is about 1.2 μm. Figure 6 , Fig. 9 , Fig.12 , Fig.16 The remaining particles are all nanometer-sized. Table 7 shows the spectrum of micron-sized precipitation strengthening phase particles. Figure 1 It is a M23(CN)6 type mixed carbonitride mainly composed of niobium nitride and does not contain tungsten, with a low C content. M is a mixture mainly composed of Nb and supplemented by elements such as V, Cr, Ni, and Fe, with a low Ni content. The spectrum of nano-scale precipitation-strengthened particles shows that they are all nano-sized mixed carbides or carbonitrides that do not contain niobium. The nano-scale precipitates are carbide-strengthening phases containing tungsten but not niobium. Their notable feature is that the Ni content is much higher than the average Ni content of the material, and most of the Ni is higher than 30%, and the Cr content is also relatively high.
[0102] From the data of energy spectrum analysis in Table 7, it can be seen that there are two different precipitation modes in this material, and V, Cr, Ni, and Fe exist simultaneously in both precipitation forms. The nano-sized second phase is a mixed carbide containing tungsten, which exists in the solid solution in the form of extremely small precipitation in the solid solution state, while the precipitates mainly composed of Nb are dispersed in the crystal in micron crystal size under thermodynamic drive. W is both a carbide-forming element and a nitride-forming element, but no trace of W is found in the precipitates mainly composed of N, indicating that at the experimental temperature of 800℃ heat treatment, W has a greater affinity for C than N, so the micron-sized precipitates are nitrides containing Nb. The discernible precipitates observed by electron microscopy at a magnification of 5000 times are nitrides without W, while the nano-sized precipitates observed by electron microscopy at a magnification of more than 25,000 times are all W-containing compounds mainly composed of C, but do not contain Nb.
[0103] Therefore, the 3040A material of this embodiment precipitates nano-scale carbides in a solid solution state, and disperses and precipitates fine particles mainly composed of nitrides in the crystal in a thermodynamic state, so that the material is strengthened, but does not diffuse to the grain boundary. It shows that W plays a good pinning role on the nano-scale carbides formed by C, while Nb and N form a mixed compound mainly composed of niobium nitride, which also does not diffuse to the grain boundary. This is the main reason why there is no second phase precipitate at the grain boundary of the austenitic stainless steel of the present invention during the heat treatment process at the sensitization temperature. Since nano-scale carbides and micron-scale nitrides are dispersed and precipitated in the crystal, the orderly arrangement between atoms is broken, causing lattice distortion, and the strength of the material is greatly improved.
[0104] Welding performance test
[0105] Although 3040A is much stronger than conventional austenitic stainless steel, its plasticity and toughness are still very good, so it can be judged that its welding performance should be very good.
[0106] The welding test was carried out using 3040A solid solution pipe, with a pipe specification of φ4.45*2.4mm.
[0107] The solid solution pipe is welded with ER347 welding wire argon arc welding. The low-magnification metallographic photo of the weld after welding is shown in Fig.18 , see the electron microscope photo of the fusion zone magnified 200 times Fig.19 , the weld on the left is dendritic, and the base material on the right is austenite with twins.
[0108] The welding test was carried out with 3040A pipes strengthened by heat treatment at 750℃, and the welding was carried out with ERNiCrMo-3(625) nickel-based welding wire with better strength and corrosion resistance. The low-magnification metallographic photos of the welding are shown in Fig. 20 No defects were found in the fusion zone, proving that the weldability is very good.
[0109] application
[0110] The 3040 austenitic stainless steel of this embodiment can be used to manufacture plates and pipes to manufacture pressure tanks, heat exchangers, etc., especially in the chemical industry, and can also be used to manufacture other pressure-bearing structural parts. Of course, it can also be used to manufacture welding wires and electrodes.
[0111] Example 2
[0112] Three groups of steel bars were rolled according to the chemical composition described in Table 8, or three groups of 347 stainless steel were subjected to electric furnace + vacuum refining and modulation according to the chemical composition described in Table 8 to obtain stainless steel materials. The temporary grade is 3470A, and the chemical composition is shown in Table 8; the mechanical properties of 3470A and 347H at 600°C high temperature tensile test are shown in Table 9.
[0113] Table 83470A Chemical composition weight percentage (%)
[0114]
[0115] Considering that 3470A is used in high temperature environment, cobalt Co and rare earth RE are added to improve the creep resistance of the material. Rare earth RE will form phosphorus P, which is easy to segregate at the grain boundary, into a phosphorus-containing rare earth compound with a high melting point, making the grain boundary binding force higher. Rare earth is added during the refining process to make a part of rare earth oxides and rare earth sulfides float up as slag inclusions, while the remaining fine rare earth oxides, rare earth sulfides and rare earth phosphides are denatured, thereby improving the material's high temperature creep resistance. The rare earth RE added during refining outside the furnace can be any single rare earth element, or a mixed rare earth mainly composed of lanthanum La and cerium Ce can be added.
[0116] The 3470A billet of test number 11 in Table 8 was rolled into a φ30 mm bar, and the high temperature tensile test and control test results after precipitation strengthening heat treatment are shown in Table 9.
[0117] Table 9 High temperature tensile test results of 3470A and 347H after holding at 600℃ for 20 minutes
[0118]
[0119] The tensile strength of 3470A in the solution delivery state at 600°C is slightly higher than that of 347H, and the yield strength is 42MPa higher than that of 347H, which is 1.285 times that of 347H; relatively speaking, the tensile strength of 3470A in the solution delivery state + 750°C heat treatment strengthening state at 600°C is greatly improved, and the yield strength is 77MPa higher than that of 347H, which is 1.52 times that of 347H.
[0120] Example 3
[0121] The heat-treatable precipitation-strengthened austenitic stainless steel of the present invention is based on all three series of austenitic stainless steels such as 304, 304L, 304LN, 321, 316, 316L, 317L, 347, 310, etc., and can be adjusted appropriately according to the microalloying element formula of the present invention to be heat-treatable and strengthened stainless steel.
[0122] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A heat-treatable precipitation-hardened austenitic stainless steel, characterized in that: The composition of the austenitic stainless steel is as follows by weight percentage: C≤0.05%; Si≤1.0%; Mn≤2.0%; S≤0.015%; P≤0.035%; Cr 16.0~20.0%; Ni 6.0~12.0%; N 0.08~0.25%; W 0.05~0.25%; V 0.05~0.25%; Any one or both of Nb and Ta 0.1-0.60%; The balance is Fe and inevitable impurities.
2. The heat-treatable precipitation-hardened austenitic stainless steel according to claim 1, characterized in that: Co is also included, and its weight percentage is 0 to 0.50%.
3. The heat-treatable precipitation-hardened austenitic stainless steel according to claim 1, characterized in that: RE is also included, and its weight percentage is 0-0.020%.
4. The heat-treatable precipitation-hardened austenitic stainless steel according to claim 1, characterized in that: The N content is 2 times or more than the C content, and C+N should be ≥0.12%.
5. A method for manufacturing austenitic stainless steel for pressure vessels capable of heat treatment and strengthening, characterized in that: The 300 series stainless steel is refined in an electric furnace and outside the furnace, and the composition is modulated according to any one of the formulas of claims 1-4.
6. A method for heat treatment and strengthening of austenitic stainless steel for pressure vessels capable of heat treatment and strengthening according to claims 1 to 4, characterized in that: After solution treatment at 1050℃, the steel is taken out of the furnace and water-cooled. After enhanced heat treatment, it is air-cooled. The enhanced heat treatment temperature is between 650 and 900℃, and the heat treatment time is 0.3-4 hours.
7. The heat treatment strengthening method for austenitic stainless steel for pressure vessels capable of heat treatment strengthening according to claim 6, characterized in that: Preferably, the heat treatment temperature is 800°C, the heat treatment time is 4 hours, and then the heat treatment is air-cooled; or the heat treatment temperature is 750°C, the heat treatment time is 1 hour, and then the heat treatment is air-cooled.
8. Use of the heat-treatable precipitation-hardened austenitic stainless steel according to claims 1 to 7 in manufacturing plates, forgings, pipes, bolts, nuts, welding wires and welding rods.
9. The use according to claim 8, characterized in that: Pressure vessels, heat exchangers, air coolers, atmospheric pressure vessels and structural products manufactured by welding the plates, forgings and pipes.
10. A welding method using the heat treatable precipitation hardened austenitic stainless steel according to claims 1 to 7, characterized in that: Welding was performed using ERNiCrMo-3 (625) nickel-based welding wire.
Citation Information
Patent Citations
Super-austenitic stainless steel and optimized design method for alloy components of super-austenitic stainless steel
CN108396223A
Super austenitic stainless steel with low precipitation phase precipitation and preparation and heat treatment method of super austenitic stainless steel
CN113943903A
Austenitic stainless steel material
CN114929919A
Preparation method of high-strength and high-plasticity austenitic stainless steel with medium nitrogen content
CN115927790A
Cited By
High-temperature-resistant high-entropy stainless steel as well as preparation process and application thereof
CN120330614A
High temperature resistant high entropy stainless steel and its preparation process and application
CN120330614B
Stainless steel fiber material and preparation method thereof
CN121518961A
A stainless steel fiber material and a method for manufacturing the same
CN121518961B